Presentasi Visual dalam Tata Kemas Sego Pincuk Terhadap Persepsi Gastronomi dan Kenikmatan - Andika Agung Sutrisno (LPPM STIKI Malang, 2024)
Food consumption has evolved from a basic human need to a lifestyle choice. Exploration of the role of packaging in shaping consumer perceptions of taste preferences, with a focus on ready-to-eat foods in banana leaf containers known as